2017
DOI: 10.1002/anie.201704119
|View full text |Cite
|
Sign up to set email alerts
|

A Direct Synthesis of Highly Substituted π‐Rich Aromatic Heterocycles from Oxetanes

Abstract: The ubiquitous use of π-rich five-membered heterocycles has driven the development of new methods for their synthesis for more than a century. Here, we disclose a general and reliable reaction manifold for the construction of highly substituted heterocycles through a facile Lewis-acid-catalyzed oxetane rearrangement. Notably, this methodology employs a keto-oxetane motif as a 1,4-dicarbonyl surrogate, which can be synthesized using robust alkylation or alkenylation reactions, and thus obviates the need to acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…In fact, two byproducts formed and were identified as β-hydroxymethyl-α-fluorolactone 14 and β-bromomethyl-α-fluorolactone 15 ( Table 4 ) [ 30 ]. This ring expansion has been already reported in the literature from oxetane-containing α,β-unsaturated carbonyl derivatives through a Lewis acid-catalyzed rearrangement [ 31 ]. When the previous conditions (HBr/AcOH) were tried (3.5 h, 0 °C to 20 °C), hydroxymethyllactone 14 (87%, Table 4 , entry 1) was the main product with traces of the corresponding acetate (4%, not shown), the bromomethyllactone 15 (8%), and alkene Z - 13 (1%).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…In fact, two byproducts formed and were identified as β-hydroxymethyl-α-fluorolactone 14 and β-bromomethyl-α-fluorolactone 15 ( Table 4 ) [ 30 ]. This ring expansion has been already reported in the literature from oxetane-containing α,β-unsaturated carbonyl derivatives through a Lewis acid-catalyzed rearrangement [ 31 ]. When the previous conditions (HBr/AcOH) were tried (3.5 h, 0 °C to 20 °C), hydroxymethyllactone 14 (87%, Table 4 , entry 1) was the main product with traces of the corresponding acetate (4%, not shown), the bromomethyllactone 15 (8%), and alkene Z - 13 (1%).…”
Section: Resultssupporting
confidence: 74%
“…The contrasting result observed with HBr/AcOH and TBAB/CSA highlighted the importance of the acidity of the medium on the reaction course of the ring-opening reaction (Scheme 5). The former, using an excess of acid (33% HBr in AcOH solution) favored the direct nucleophilic attack (path b) leading to lactone 14, whereas the latter in the presence of TBAB/CSA allowed bromide addition on the same side of the fluorine atom (path a) leading to lactone 15 [31]. However, the reaction can be stopped at the alcohol stage when performed in the presence of BF 3 •Et 2 O instead of CSA to afford alkene Z-13 as the major product.…”
Section: Resultsmentioning
confidence: 99%
“…As already mentioned, oxetanes are excellent building blocks for five‐membered heterocycles. Vanderwal et al recently reported the synthesis of π‐rich aromatic heterocycles from oxetanes Against this backdrops, we conducted the reaction of an amide appended oxetanes in the presence of BF 3 · OEt 2 in toluene. The reaction provided an interesting product, viz., as 5‐methylene‐1 H ‐pyrrol‐2(5 H )‐one derivative 6a (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The oxetane ring provides additional synthetic opportunities. 26 Since several groups have discovered oxetane desymmetrizations in recent years, 27 we decided to highlight the general utility of our oxetanyl fluorides with a modified Lewis acid promoted ring opening protocol. 28 After some reaction optimization using benzylthiol as the nucleophile we obtained ( R,S )- 13 in 68% yield, 95% ee and with >99:1 dr from ( R )- 3a .…”
mentioning
confidence: 99%